2022
DOI: 10.1007/s11356-022-24832-6
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetric and long-run effect of energy productivity on environmental quality in Ireland

Abstract: This study aims to examine the long-run asymmetric impact of energy productivity on environmental quality in Ireland. The data set covers the period from 1990Q1 to 2019Q4. Although the border issue has been the source of contention and terrorism for decades in Ireland, the country is conscious of modern innovations and has a coherent body of environmental law. Ireland’s goal is to achieve 80% of its electricity as renewable energy and reduce carbon emissions by 51% in 2030. Unlike earlier studies, the novelty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Recently introduced new phenomenon named "Energy productivity" refers to all economic benefits derived from consuming total energy resources. We measure it as $/MJ and it refers to total primary energy use of an economy (Kirikkaleli et al, 2023). However this phenomenon is relatively less explored in the existing literature in terms of its role in determining environmental quality.…”
Section: Energy Productivity and Pollution Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently introduced new phenomenon named "Energy productivity" refers to all economic benefits derived from consuming total energy resources. We measure it as $/MJ and it refers to total primary energy use of an economy (Kirikkaleli et al, 2023). However this phenomenon is relatively less explored in the existing literature in terms of its role in determining environmental quality.…”
Section: Energy Productivity and Pollution Emissionsmentioning
confidence: 99%
“…Like Abbasi et al (2023) estimated the effect of energy productivity on consumption based CO 2 emission in Iceland over the period from 1995 to 2019. Fourier ARDL model was in the study that revealed that energy productivity had negative effect on consumption based carbon emission in Iceland Kirikkaleli et al (2023). estimated the impact of energy productivity on environmental pollution in Ireland over quarterly period 1990-2019.…”
mentioning
confidence: 99%